Tableaux d'une histoire. - Bourel, Michel; Marland, Philippe; Réol, Jean-Marc; Vauzelle, Michel (Nice : Villa Arson, 1998)
Aillaud, Gilles ; Arroyo, Eduardo ; Autard, Georges ; Barré, Martin ; Bart, Cécile ; Bélorgey, Yves ; Ben ; Bertrand, Jean-Pierre ; Bioulès, Vincent ; Blais, Jean-Charles ; Bustamante, Jean-Marc ; Castellas, Denis ; Charvolen, Max ; Clavère, Frédéric ; Cremonini, Leonardo ; Degottex, Jean ; Dezeuze, Daniel ; Dolla, Noël ; Dubuffet, Jean ; Ducaté, Marie ; Figarella, Dominique ; Garouste, Gérard ; Graham, Rodney ; Gronon, Philippe ; Hains, Raymond ; Hantaï, Simon ; Hartung, Hans ; Hyber, Fabrice ; Jaccard, Christian ; Keller, Art ; Klasen, Peter ; Klemensiewicz, Piotr ; Kusnir, Carlos ; Gac, Jean Le ; Mayeux, Philippe ; Mencoboni, Didier ; Mitchell, Joan ; Mogarra, Joachim ; Monory, Jacques ; Montigone, Jean-Louis ; Moulène, Jean-Luc ; Penck, A.R. ; Piffaretti, Bernard ; Pinaud, Pascal ; Pincemin, Jean-Pierre ; Salomone, Yven ; Schiess, Adrian ; Soulages, Pierre ; Stauth, Pascale ; Queyrel, Claude ; Tàpies, Antoni ; Tatah, Djamel ; Teisseire, Cédric ; Telemaque, Hervé ; Thupinier, Gerald ; Traquandi, Gérard ; Viallat, Claude ; Voss, Jan
biografie
Tableaux d'une histoire, Villa Arson, Nice, 24 octobre - 19 décembre 1998
Frans
boek